A atuação da terapia ocupacional na atenção básica a saúde - LOBATO, Alesson da Silva (2023)
Introduction: Basic Care (BC) is the primary level of health care that provides access to the entire national system to attend the population‘s needs, in order to organize both basic and specialized services for promotion, maintenance and improvement of health. Therefore, Occupational Therapy is a profession of supreme importance in this service because its actions contribute to the prevention of diseases/injuries and supporting health promotion. Objective: Understand the role of Occupational Therapy in Basic Health Care. Methods: This is an integrative review of the literature, through the databases: CAPES Journal‘s Portal, Occupational Therapy Journal of the University of São Paulo, Brazilian Interinstitutional Journal of Occupational Therapy and Brazilian Journal of Occupational Therapy. The studies were analyzed by the relevance test I and II, the data were processed in the IRAMUTEQ software and analyzed by word cloud and similitude. Results/Discussion: The sample consisted of 25 studies, which indicate that the Occupational Therapy in BC should act along with the population with characteristics of mental suffering, deficiencies and disabilities, aiming to mediate in the singularity and subjectivity of the subject, in this way, the occupational therapists presents elements that can effectively contribute to improving the health of the population. It is also worth mentioning the importance of new publications that contribute to the scientific community.